1997
DOI: 10.1128/jvi.71.5.4176-4180.1997
|View full text |Cite
|
Sign up to set email alerts
|

Echovirus 1 replication, not only virus binding to its receptor, VLA-2, is required for the induction of cellular immediate-early genes

Abstract: Induction of immediate-early genes c-jun, junB, and c-fos was demonstrated during echovirus 1 infection in a human osteogenic sarcoma (HOS) cell line. Tenfold induction was seen at 10 h postinfection, corresponding approximately to the end of the first replication cycle of the virus. Echovirus 1 uses VLA-2 integrin as its cellular receptor, and ligand binding by integrin is known to trigger signal transduction pathways ultimately activating immediate-early genes. In the present study, however, VLA-2 binding al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Type I collagen and EV1 share the same cellular receptor but induce IE genes by different mechanisms Integrin-matrix interaction is known to mediate integrin clustering and regulate IE genes (Schwartz et al, 1995). EV1 binds to ␣ 2 ␤ 1 integrin, a major collagen receptor in many cells, and we have shown that infection induces mRNA levels of IE genes and that active viral macromolecular synthesis is needed for the induction (Huttunen et al, 1997). To further study this phenomenon, we analyzed junB and c-jun gene activation after adding soluble collagen or EV1 to HOS p␣ 2 AW cells.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Type I collagen and EV1 share the same cellular receptor but induce IE genes by different mechanisms Integrin-matrix interaction is known to mediate integrin clustering and regulate IE genes (Schwartz et al, 1995). EV1 binds to ␣ 2 ␤ 1 integrin, a major collagen receptor in many cells, and we have shown that infection induces mRNA levels of IE genes and that active viral macromolecular synthesis is needed for the induction (Huttunen et al, 1997). To further study this phenomenon, we analyzed junB and c-jun gene activation after adding soluble collagen or EV1 to HOS p␣ 2 AW cells.…”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, the cells did not spread when plated onto EV1 (not shown), which was in contrast to cells plated onto collagen. Thus, despite the fact that the cells use ␣ 2 ␤ 1 integrin in both collagen and EV1 binding (Huttunen et al, 1997), ligand binding can lead to different cellular consequences. To study whether IE genes are induced when the HOS p␣ 2 AW cells are bound to EV1 without internalization of the virus, we carried out an assay in which cell culture dishes were coated with EV1 or COL I, the cells were allowed to attach for 5 h, and then the levels of c-jun and junB mRNAs were analyzed by Northern blotting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the inhibition of histone demethylase has been shown to block HSV and VZV replication (Liang et al, 2009) and VZV ORF 63 has been shown to regulate histone levels in infected cells (Ambagala et al, 2009). Several of the other upregulated transcription factors that were involved with chromatin assembly such as CFOS, JUNB and JUND were reported to be upregulated with other viral infections such as kaposi's sarcoma-associated herpesvirus (Xie et al, 2008), Epstein-barr virus (Song et al, 2004) measles (Helin et al, 2002), JC virus (Sadowska et al, 2003) and echoviruses (Huttunen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%